Factors Associated With Past-year and Lifetime Prevalence of Cannabis Withdrawal: A Secondary Analysis. Issue 3 (22nd September 2022) - Bahji, Anees; Gorelick, David A.
ABSTRACT: Background: Cannabis withdrawal syndrome (CWS) is a recognized psychiatric disorder that can interfere with recovery from cannabis use disorder (CUD). Objectives: To identify factors differentially associated with the prevalence of lifetime and past-year CWS. Methods: We conducted a secondary analysis of a 2020 systematic literature review on the prevalence of CWS among people with regular cannabis use or moderate-severe CUD and conducted new meta-analyses separately for lifetime and current (past-year) CWS prevalence. Results: The meta-analyses used 51 studies, including 4 additional studies not used in the 2020 meta-analyses. The overall prevalence of CWS was 65.4% (95% CI, 50.1%–78.1%) for lifetime (based on 22 studies) and 30.1% (95% CI, 23.4%–37.7%) for current (based on 29 studies). The only 2 factors that were significantly associated with lifetime CWS prevalence in multivariable meta-regression were sample source (inpatient >outpatient >nonclinical populations) and cannabis use frequency at baseline (daily >less-than-daily >not reported). However, current CWS prevalence was associated with 9 additional factors: study design (longitudinal cohort >cross-sectional), source of CWS diagnostic information (self-related or informant-rated >clinician-rated), geographic region (South America >rest), method of CWS diagnosis (multi-item rating instrument >generic question), lifetime tobacco use disorder comorbidity (present >absent), treatment-seeking status for CUD (treatment-seeking >nonseeking), race/ethnicity (Latino/Hispanic or Black >White), sex (male >female), and age (younger >older). Conclusions: Our study found that current CWS had 11 factors associated with prevalence, while lifetime CWS had only 2. These different associations do not imply causality but suggest possible differences in factors that promote or protect against the development of CWS, which warrants further study. Abstract : Contexte: Le syndrome de sevrage du cannabis (SSC) est un trouble psychiatrique reconnu qui peut interférer avec le rétablissement d'un trouble lié à l'usage du cannabis (TCC). Objectifs: Identifier les facteurs et leurs différences associés à la prévalence du SSC au cours de la vie et de l'année précédente. Méthodes: Nous avons effectué une analyze secondaire d'une revue systématique de la littérature de 2020 sur la prévalence du SSC chez les personnes ayant une consommation régulière de cannabis ou un trouble de consommation de cannabis modéré à sévère et nous avons effectué de nouvelles méta-analyses distinctes pour la prévalence du SSC au cours de la vie entière et du SSC actuel (année passée). Résultats: Les méta-analyses ont utilisé 51 études, dont quatre études supplémentaires non utilisées dans la méta-analyses de 2020. La prévalence globale du SSC était de 65, 4 % (IC à 95%, 50, 1–78, 1%) pour la vie entière (basé sur 22 études) et 30, 1 % (IC à 95%, 23, 4%–37, 7%) pour la vie actuelle (basé sur 29 études). Les deux seuls facteurs significativement associés à la prévalence du SSC au cours de la vie dans la méta-régression multivariable était la source de l'échantillon (patient hospitalisé; patient externe; populations non cliniques) et la fréquence de la consommation de cannabis au départ (quotidienne; moins que quotidiennement; non déclaré). Cependant, la prévalence actuelle du SSC était associée à neuf facteurs supplémentaires: le plan d'étude (cohorte longitudinale et transversale), la source d'information sur le diagnostic du SSC (auto-évaluées ou évaluées par un intervenant; évaluées par un clinicien), région géographique (Amérique du Sud; autre), méthode de diagnostic du SSC (instrument d'évaluation multi-items; question générique), comorbidité du trouble du tabagisme au cours de la vie (présent; absent), le statu de recherche de traitement pour le TCC (recherche de traitement; non-recherche de traitement), race/ethnicité (Latino/Hispanique ou Noir; Blanc), le sexe (homme; femme) et l'âge (jeune; âgé). Conclusion: Notre étude a révélé que le SSC actuel comportait 11 facteurs associés à la prévalence, tandis que le SSC au cours de la vie entière n'en avait que deux. Ces associations différentes n'impliquent pas de causalité mais suggèrent des différences possibles dans les facteurs qui favorisent ou protègent contre le développement du SSC, ce qui justifie une étude plus approfondie.